PENGARUH LIQUIDITY, LEVERAGE, TOTAL ASSET TURNOVER, DAN FEMALE DIRECTOR TERHADAP FINANCIAL PERFORMANCE - Selsha Gabriella Soeandi; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2023)
This research aims to have an empirical test on the effect of liquidity, leverage, total asset turnover, and female director toward financial performance on manufacturing firm listed consistently on the Indonesia Stock Exchange during the period of 2017-2020. Sample was selected using purposive sampling method. The total number of samples used was 452 samples. The research data was obtained from financial statements and annual reports, which collected in Microsoft Excel 2016. Data processing techniques using multiple regression analysis and processed by Eviews 12. This research revealed that partially liquidity, leverage, and total asset turnover have positive impact on financial performance, while female director has negative impact on financial performance. Meanwhile,simultaneously the four independent variables have an impact on financial performance. The implication of this study is the need to increase the liquidity, leverage, total asset turnover, and decrease the presence of female director to improving the company’s financial performance which will bring a good signal for investors to have an investment activity.